Effect of Co-Fertilizer Application and Dolomite Amendments on Yield and Grain Quality of Rice Grown on Post-Active Acid Sulfate Soil - Saychol Sukyankij; Sopida Sukyankij; Thanawan Panich-pat (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2023)
Improving the grain yield of rice and increasing the availability of nutrients in cultivated soils are important goals of sustainable agriculture. This study was aimed to determine the effects of different fertilizer applications and dolomite amendments on rice yield, quality, and soil fertility after plantation in post-active acid sulfate soil in the Phra Nakhon Si Ayutthaya province, Thailand. A randomized complete block design (RCBD) with six treatments and three replications was employed, i.e. T1 (no fertilizer); T2 (fertilizer at the rate of the farmers’ practice, CFFMP); T3 (fertilizer at the rate of site-specific nutrient management, SSNM); T4 (SSNM+organic fertilizer, OF); T5 (SSNM+dolomite, DM); and T6 (SSNM+OF0.5+DM0.5). Our results indicated that the treatment of SSNM+DM provided the highest grain yield (6,171 kg/ha). For the quality of rice grain, the highest protein level was found in the treatment of CFFMP (80.2 g/kg). Application of fertilizer according to the SSNM+OF treatment resulted in higher soil organic matter, available phosphorus, and exchangeable potassium in the soil after rice cultivation than in other treatments. The results suggested that the application of SSNM+DM and SSNM +OF0.5+DM0.5 was the best options for improving rice yield in this area.